Spatial Analyses of Low Birth Weight Incidence, Indonesia - Donal Donal; Hartono Hartono; Muhammad Hakimi; Ova Emilia (Indonesian Journal of Geography, 2018)
The etiology of Low Birth Weight (LBW) in Murung Raya is still unclear. This study aimed to find out the relationship between environmental and health behavior risk factors of LBW in Murung Raya. 150 women were recruited through the incidence data 2013- 2014, and the questionnaires, medical records, and geographic data were measured by McNemar, ANOVA, logistic, IRR, MI, z (Gi), and NNI tests. Bivariate analysis showed significant correlation of LBW with TBA care OR= 10, drinking popa OR= 5, smoking OR= 6.1, and accessibility OR = 2.3, with adjusted OR for TBA care OR= 32.78, ANC OR= 27.52 revealing trend lines with ANOVA F=49, and clustering RR=7, MI >0 (four clusters), z (Gi) >1 (two high clusters), and NNI>1 (two high clusters). The spatial analysis provided greater statistical power to detect an effect that was not apparent in the case-control study. This study suggests that preventions, interventions and treatment for LBW not only be conducted by the current epidemiology approach but also by new modern geographic positioning analysis.